Identification of an autoinhibitory mechanism that restricts C1 domain-mediated activation of the Rac-GAP α2-chimaerin - Colón González, Francheska (2008)
Chimaerins are a family of GTPase activating proteins (GAPs) for the small G-protein Rac that have gained recent attention due to their important roles in development, cancer, neuritogenesis, and T-cell function. Like protein kinase C isozymes, chimaerins possess a C1 domain capable of binding phorbol esters and the lipid second messenger diacylglycerol (DAG) in vitro. Here we identified an autoinhibitory mechanism in α2-chimaerin that restricts access of phorbol esters and DAG, thereby limiting its activation. Although phorbol 12-myristate 13-acetate (PMA) caused limited translocation of wild-type α2-chimaerin to the plasma membrane, deletion of either N- or C-terminal regions greatly sensitize α2-chimaerin for intracellular redistribution and activation. Based on modeling analysis that revealed an occlusion of the ligand binding site in the α2-chimaerin C1 domain, we identified key amino acids that stabilize the inactive conformation. Mutation of these sites renders α2-chimaerin hypersensitive to C1 ligands, as reflected by its enhanced ability to translocate in response to PMA and to inhibit Rac activity and cell migration. Notably, in contrast to PMA, epidermal growth factor promotes full translocation of α2-chimaerin in a phospholipase C-dependent manner, but not of a C1 domain mutant with reduced affinity for DAG (P216A-α2- chimaerin). Therefore, DAG generation and binding to the C1 domain are required but not sufficient for epidermal growth factor-induced α2-chimaerin membrane association. Our studies suggest a role for DAG in anchoring rather than activation of α2-chimaerin. Like other DAG/phorbol ester receptors, including protein kinase C isozymes, α2-chimaerin is subject to autoinhibition by intramolecular contacts, suggesting a highly regulated mechanism for the activation of this Rac-GAP.